Improving panicle blast resistance and fragrance in a high-quality japonica rice variety through breeding - Junhua Ye; Junhua Ye; Kai Wang; Yi Wang; Zhipeng Zhao; Ying Yan; Hang Yang; Lixia Zhang; Lixia Zhang; Zejun Hu; Zejun Hu; Zhenying Shi; et al. (Frontiers in Plant Science)
IntroductionHuruan1212 (HR1212) is well-regarded for its superior eating and cooking quality in the lower reaches of the Yangtze River in China. Still, its high susceptibility to rice panicle blast and lack of fragrance have limited its further spread and utilization. Pigm and Pi-ta are two dominant genes known for their stable broad-spectrum resistance against rice blast fungus Magnaporthe oryzae, while badh2 is the crucial gene that regulates rice aroma.MethodsIn this study, we utilized a molecular marker-assisted selection backcrossing strategy to introduce Pigm, Pi-ta, and badh2 into introgressed lines employing re-sequencing for precise genetic background selection.ResultsFinally, we selected three introgressed lines, including two that carry Pigm with the highest background recovery rates, showing eating and cooking qualities similar to those of HR1212, and one line that pyramids Pigm, Pi-ta, and badh2, which features a strong aroma. They all displayed significantly enhanced resistance to panicle blast and improved yield compared to HR1212.DiscussionIn conclusion, this study expanded the germplasm resources of japonica, providing a material foundation for enhancing breeding programs aimed at developing rice blast-resistant and high-quality fragrant japonica varieties. Additionally, the study demonstrated that integrating molecular markers and re-sequencing can inform breeders’ decision-making more precisely and efficiently.